Maximum Value Search and Polynomial Fit Metal Artifact Reduction Algorithm - Li Yuanjin; Wang Tao (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Metal artifacts seriously degrade CT image quality, and even restrict the using of computed tomography imaging. In this paper, the authors propose a metal artifact reduction algorithm to suppress the metal artifacts in CT image. The metal artifact reduction algorithm, in this paper, includes six steps: coarse metal implant segmentation, nearly accurate metal object segmentation, forward projection, polynomial-based fit, adaptive scaling as well as final image reconstruction. Experiment on image showed that RMSEs between the corrected image using polynomial fit, nearest interpolation, linear interpolation and spline interpolation and ideal model image are 0.20912, 0.33252, 0.24257 and 0.26791, respectively. It has the potential to greatly improve the quality of CT image and suppress the metal artifacts. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.3623